Youth work ethics - Roberts, Jonathan (Exeter : Learning Matters, 2009)
Ethics are a key issue for youth workers because youth work tries to do something good with young people who are moving to autonomy. This book considers the establishment of organisations, by neighbourhoods and networks, to express an ethical purpose among young people.
1. Why worry about ethics in youth work? -- 2. Values: association and listening -- 3. Values: equality -- 4. Values: participation -- 5. Developing ethical reflection by young people -- 6. Youth workers and ethical conduct -- 7. Youth work organisations as ethical projects -- 8. Ethics and research in youth work -- 9. Setting ethical priorities and explaining them.
Includes bibliographical references and index.
Keywords: Social work with youth -- Moral and ethical aspects; Youth workers -- Professional ethics